Carcinoide gástrico: actualización y controversias - Marambio G., Andrés; de la Llera K., Juan Francisco (Revista Hospital Clínico Universidad de Chile, 2013)
Gastric carcinoid corresponds to a rare malignancy, whose frequency increases with time. Several arguments attempt to explain this change. It´s derived from one type of gastric neuroendocrine cell, the enterochromaffin-like cells. Various classifications have been used, however, the 1993 classification of Rindi remains the most used, which includes 3 types of gastric carcinoid based on its associated conditions, frequency, morphology, pathophysiology and prognosis. Also, a fourth type has been recognized that would represent a more aggressive neoplasm, like an adenocarcinoma. Diagnosis requires an upper gastrointestinal endoscopy, biopsies and ideally levels of chromogranin A as a serum marker. Once the type of gastric carcinoid is established the proper management can range from simple observation, endoscopic resection or surgery. In the case of metastatic disease a number of other treatments that might even eventually include liver transplantation are added. It is still much to learn from this disease, with many controversies in the pathophysiology and management, some of which we will try to clarify in the following article.